Modeling Urban System Sustainability as Impacting Energy System - Dash, Nibedita; Balachandra, P. (Journal of Environmental Accounting and Management, 2026)
Increasing urbanization, in terms of growth in population as well as geographical spread, in developing countries has significant implications for the transport sector. They are manifested as two important indicators – increases in traffic volume and energy consumption. The energy resource constraints, threat of climate change and infrastructure inadequacies have transformed the above two into serious challenges and thus needing immediate attention of planners and policy makers. Adding to the above challenges, recent times have witnessed creation of more sub-urban centers with dispersed activities and hence requiring increased travel needs with higher traffic volumes. However, there is inadequate research in understanding the casual interactions among various agents (or subsystems) of an urban system in relation to transport system, its impact on energy system and consequently on the sustainability of the system as a whole. In this paper, we discuss an attempt to study such interactions by dividing the urban system into many sub-systems, linking these with mobility (or transport) sub-system and then analyzing its combined effect on energy system. The conceptual framework is developed on the premise that each subsystem will have an input and an output and these can be modeled through indicators. Further, these indicators have been mapped into three dimensions of sustainability, namely, social, economic and environmental. Appropriate indicators are chosen to represent the three dimensions. The framework has been validated using data from 36 Indian cities. The extent of sustainability in each dimension is assessed against energy subsystem represented by output indicators. Overall measure of urban system sustainability is established as an average effect of each dimension of sustainability. We contribute in developing new understanding of the underlying role of urban system dynamics towards sustainability, by disintegrating it into residential, employment and mobility subsystems and their impact on the energy system.